Three-dimensional digital applications for implant space planning in orthodontics: A narrative review - Bianchi, Jonas [UNESP]; Mendonca, Gustavo; Gillot, Maxime; Oh, Heesoo; Park, Joorok; Turkestani, Najla Al; Gurgel, Marcela; Cevidanes, Lucia (Elsevier, 2022)
In the digital dentistry era, new tools, algorithms, data science approaches, and computer applications are available to researchers and clinicians. However, there is also a strong need for better knowledge and understanding of multisource data applications, including three-dimensional imaging information such as cone-beam computed tomography images and digital dental models for multidisciplinary cases. In addition, artificial intelligence models and automated clinical decision systems are rising. The clinician needs to plan the treatment based on state-of-the-art diagnosis for better and more personalized treatment. This article aimed to review basic concepts and the current panorama of digital implant planning in orthodontics, with open-source and closed-source tools for assessing cone-beam computed images and digital dental models. The visualization and processing of the three-dimensional data allow better implant planning based on bone conditions, adjacent teeth and root positions, and the prognosis of the case. We showed that many tools for assessment, segmentation, and visualization of cone-beam computed tomographic images and digital dental models could facilitate the treatment planning of patients needing implants or space closure. The tools and approaches presented are toward personalized treatment and better prognosis, following the path to a more automated clinical decision system based on multisource three-dimensional data, artificial intelligence models, and digital planning. In summary, the orthodontist needs to analyze each patient individually and use different software or tools that better fit their practice, allowing efficient treatment planning and satisfactory results with an adequate prognosis.
Keywords: CBCT; Digital dental models; Digital dentistry; Implant planning